Evaluasi Pelaksanaan Penerimaan Peserta Didik Baru (PPDB): (Segi Produk Pelaksanaan) di Kuttab Ibnu Abbas Klaten - Laila wulan wulandari; Purwanto Purwanto; Andi Arif Rifa’i; Nur Fadhilah Al-Karimah (Journal of Contemporary Islamic Education, 2023)
The study was conducted to evaluate the results of the implementation of PPDB in Kuttab Ibn Abbas Klaten. The evaluation was carried out using qualitative data. Evaluation is carried out by comparing the appearance of the program with the criteria. This research is an evaluation method research, with a qualitative approach. The study was conducted to evaluate the results of the implementation of PPDB in Kuttab Ibn Abbas Klaten. The evaluation was carried out using qualitative data. Evaluation is carried out by comparing the appearance of the program with the criteria. Based on the results of the study, it can be concluded that, Kuttab Ibn Abbas Klaten has various problems where the certainty of acceptance time so that it has sufficient obstacles to make many shortcomings in implementation, but can be well controlled because of the coordination between the principal of the chief executive well, so that good programs in the provision of PPDB programs, school programs, provision of PPDB facilities and provision of PPDB facilities because they are seen From the field results show the satisfaction of parents in sending their children to school.